Knowledge, Attitudes, and Practices of Telemedicine in Ophthalmology in a Tertiary Hospital A Cross-Sectional Survey - Angelica Antoinette C. Vega, MD; Sherman O. Valero, MD, DPBO (Philippine Journal of Ophthalmology)
Objective: The purposes of this study were to (1) describe the perceptions and practices of telemedicine among ophthalmologists in a tertiary hospital; and (2) evaluate knowledge, satisfaction, and perceived patient outcomes in using telemedicine to provide eye care in a time of a global pandemic.